Involvement of mast cells in gastritis caused by Helicobacter pylori: a potential role in epithelial cell apoptosis. Issue 6 (8th June 2007) - Hofman, Véronique; Lassalle, Sandra; Selva, Eric; Kalem, Kheira; Steff, Adrien; Hébuterne, Xavier; Sicard, Dominique; Auberger, Patrick; Hofman, Paul
Abstract : Background: The role(s) of mast cells (MC) in gastric mucosal inflammation caused by Helicobacter pylori is (are) still debated. Aim: To determine whether there is an association between MC density and epithelial cell apoptosis in antral gastric mucosa infected by H pylori . Patients and methods: Biopsy specimens from 122 H pylori -positive subjects with chronic active gastritis, 84 patients with non-steroidal anti-inflammatory drug-induced gastritis and 48 volunteers were included. H pylori genotypes were determined by PCR amplification of bacterial cultures. Immunohistochemical analysis was performed on tissue microarrays with anti-CD117, anti-chymase, anti-tryptase, anti-myeloperoxidase, anti-Bcl-2, anti-Bcl-x, anti-Bax and anti-caspase 3 antibodies. Results: Of the 122 patients infected with H pylori, 76 (62.3%) harboured cagA positive strains. H pylori isolates belonged to the vacAs1/m1 genotype in 82 (67%) cases, to the vacAs2/m2 genotype in 23 (18.8%) cases and to the vacAs1/m2 genotype in 17 (13.9%) cases. 61 (50%) H pylori isolates were babA2 +. In patients infected with H pylori, the density of MC, and in particular the number of MC-associated epithelial cells, was correlated with a high number of apoptotic epithelial cells. Moreover, the density of MC was correlated with the number of neutrophils infiltrating the antral gastric mucosa, and was strongly increased in patients infected with cagA, vacAs1/m1 and babA2 positive strains. Conclusions: Taken together, these data show that the density of MC can be considered as a histopathological criterion of gastritis activity in patients infected with H pylori .